Rectobuntonia miranda and Krithe keyi relative abundances and clay mineral and grain-size analysis at sites in the Gulf of Cadiz - Moal-Darrigade, Paul; Ducassou, Emmanuelle; Alvarez-Zarikian, Carlos A; Carbonel, Pierre; Hanquiez, Vincent; Bout-Roumazeilles, Viviane; Mulder, Thierry; Perello, Marie-Claire; Giraudeau, Jacques (PANGAEA, 2025)
The present dataset comprises micropaleontological and sedimentological analyses on cores MD99-2337 (598 mbsl), IODP U1390 (992 mbsl), and CADKS24 (1,316 mbsl). These cores, collected as part of the oceanographic expeditions IMAGES-V/GINNA (1999), Integrated Ocean Drilling Program (IODP) Expedition 339 (2011-2012), and CADISAR 1 (2004), respectively, are distributed along a bathymetric transect from 600 to 1300 water depth. This study specifically addresses changes in Mediterranean Outflow (MOW) paleo-depths and paleo-velocities in the Gulf of Cadiz using independent and complementary proxies, ostracod species from Mediterranean origin, clay mineral associations and grain-size analysis. The here presented data comprises: ostracod abundances in valves per gram, Rectobuntonia miranda and Krithe keyi relative abundances in %, clay mineral assemblages in %, cohesive fine particles measuring less than 10 µm in %, and sortable silt in µm.
Keywords: Clay minerals; Grain-size analyses; Gulf of Cadiz; MOW; ostracods